DESCRIPTION OF ISSUES RELATED TO INTERNATIONAL RELATIONS IN THE WORKS OF IMAM AL-SARAKHSI - Shukrullo Juraev (Sciental Journals Publishing, 2025)
This article provides a comprehensive analysis of the scholarly contributions of Imam Shams al-A’imma al-Sarakhsi (d. 1090) to the discipline of Islamic international law (siyar). Focusing primarily on his renowned commentary Sharh al-Siyar al-Kabir, the paper explores how al-Sarakhsi elaborated on the foundational legal principles laid down by earlier Hanafi scholars such as Abu Hanifa, Abu Yusuf, and especially Muhammad al-Shaybani. The study delves into al-Sarakhsi’s treatment of international relations, including the conduct of war (jihad), the terms of peace treaties, the legal status of non-Muslim citizens (dhimmis), the role of envoys and diplomacy, and the ethical constraints on warfare and treatment of prisoners. The article also addresses the historical significance of Sharh al-Siyar al-Kabir as one of the most detailed and structured works in the field of siyar, and evaluates its influence on both classical Islamic jurisprudence and contemporary comparative legal thought. Special attention is given to how modern scholars, such as Najib Armanazi and Khalid Ramadan Bashir, have assessed the relevance of al-Sarakhsi’s jurisprudence in the context of international legal theory. Furthermore, the article draws parallels between al-Sarakhsi’s legal reasoning and that of Western thinkers like Hugo Grotius and Thomas Aquinas, demonstrating that many legal norms found in modern international law were already articulated in classical Islamic legal texts. Through textual analysis and historical contextualization, this study establishes Imam al-Sarakhsi’s pivotal role in shaping Islamic perspectives on international relations and underscores the enduring relevance of his thought for current debates in legal ethics and the laws of war and peace.
Keywords: Imam al-Sarakhsi, Islamic international law, siyar, Sharh al-Siyar al-Kabir, jihad, treaties, dhimmi, Hanafi school, Muhammad al-Shaybani, Islamic jurisprudence, comparative legal studies, Grotius.